Opportunities for Greenways Through Development of Ecological and Green Corridor Landscape Planning in Hungary - Attila Csemez; Judit Bárcziné Kapovits (Fábos Conference on Landscape and Greenway Planning, 2013)
In the specialist literature on landscape design, greenways are multi-functional routes which optimally have both recreational and ecological functions. The recreational function of greenways is primarily use by pedestrians, cyclists and horse-riders. The ecological role of greenways means that optimally they are part of a given landscape’s ecological system. In the course of our research – taking into account the natural, social and economic conditions, as well as landscape and design precedents – we are seeking answers to questions within the following categories: (1) justifications for the creation of greenways in Hungary; (2) the geographical areas in which greenways may be required; (3) the type of landscape features that facilitate the establishment of greenways.
Keywords: greenways; opportunities; landscape planning; corridor; hungary; development